Development of Appropriate Strategies for the Use of Wastewater in Agricultural Activities (Case Study: Belan Village, Kurdistan Province, Iran) - shahpar Geravandi; Fatemeh Ghorbani; Siavosh Ghanbari (محیط زیست و مهندسی آب, 2022)
Due to the increase in population and more wastewater production and the existence of limited water resources, the use of human wastewater in agricultural activities is a necessity. The present qualitative research, while investigating the consequences of the use of wastewater, seeks to develop appropriate strategies for the use of wastewater in agricultural activities in the village of Belan, Kurdestan province. Using the criterion-based sampling method, 14 farmers were studied as a sample. Semi-structured interviews and direct observation were used to collect information. The validity of the findings was confirmed by triangulation and Qualitative data analysis was performed using Maxqda software. The results showed that increasing the area under cultivation, increasing yield, water supply, and less use of chemical fertilizers are positive impacts of wastewater use. Moreover, the increase of pests, increase of weeds, occurrence of physical and mental disorders, unpleasant odor, a decrease in soil quality, pollution of the rural environment, and increase in migration are among the negative impacts of using wastewater. The use of standards for wastewater treatment, preparation of soil sensitivity map, use of the appropriate irrigation method, attention to plant type, and disinfection of wastewater are also among the strategies suggested by users.